Ecology and physiology of selected mangrove species under elevated sea level / Mariyam Zarana Rasheed - Rasheed, Mariyam Zarana (2012)
Climate change components such as sea level rise and increased atmospheric carbon dioxide is likely to affect plant communities at various scales. Mangrove ecosystems are highly threatened by the sea level rise as a result of prolonged waterlogging. Four sets of experiments were set up to study the ecology and physiology of Avicennia alba, Avicennia marina and Bruguiera parviflora under simulated sea level rise. In elevated sea level, A. alba and B. parviflora indicated similar responses with initial height increments, decreased stem diameter and leaf formation; and increased leaf fall. The total biomass and relative growth rates (RGR) also decreased. Similarly, physiological parameters such as assimilation, stomatal conductance and carbon sequestration decreased. In contrast, A. marina had stem height increment through out the study period but had decreased diameter increment under elevated sea levels. Leaf formation and leaf fall was insensitive to tidal flooding. Likewise, biomass and RGR of A. marina remained unaffected by the tidal treatments. Physiological parameters and carbon sequestration of A. marina was affected to a lesser extent than A. alba and B. parviflora. In addition, elevated sea level affected soil physical characteristics. The differences varied significantly between species where soil redox potential and pH was highly reduced in A. alba and B. parviflora. The growth and physiological responses of these three species indicate that A. alba and B. parviflora are more sensitive to sea level rise, while A. marina is better adapted to the associated stresses. These results correspond with the distribution of these three species along the intertidal zone where A. marina is found at the lower intertidal zones, while A. alba and B. parviflora occupy the landward margins of the mangrove forests.